2017
DOI: 10.1002/2211-5463.12273
|View full text |Cite
|
Sign up to set email alerts
|

The asparagine 533 residue in the outer pore loop region of the mouse PKD2L1 channel is essential for its voltage‐dependent inactivation

Abstract: Voltage‐dependent inactivation of ion channels contributes to the regulation of the membrane potential of excitable cells. Mouse polycystic kidney disease 2‐like 1 ( PKD 2L1) forms voltage‐dependent nonselective cation channels, which are activated but subsequently inactivated in response to membrane depolarization. Here, we found that the mutation of an asparagine 533 residue (N533Q) in the outer pore loop region of PKD 2L1 caused a marked increase in outward curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…Quinine is a cinchona alkaloid exhibiting an antimalarial activity, which has been used as a standard bitter tastant in taste perception research 20 . In the present study, we investigated whether a bitterant, quinine, affects the constitutive PKD2L1 currents recorded in whole-cell patch-clamp recordings [17][18][19] . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Quinine is a cinchona alkaloid exhibiting an antimalarial activity, which has been used as a standard bitter tastant in taste perception research 20 . In the present study, we investigated whether a bitterant, quinine, affects the constitutive PKD2L1 currents recorded in whole-cell patch-clamp recordings [17][18][19] . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PKD2L1 channel exhibits voltage-dependent or Ca 2+ -dependent inactivation. In our previous study, the outer pore loop region of the PKD2L1 channel is demonstrated to be essential for its voltage-dependent inactivation 19 . On the other hand, the Ca 2+ -dependent inactivation is reported to be due to Ca 2+ -binding in the selectivity filter of the PKD2L1 channel 23 .…”
Section: Avoidance Of Quinine-containing Water By Mice In Vivomentioning
confidence: 96%
See 2 more Smart Citations
“…In TRPA1 channels, L906 in the pore helix is considered to be essential for voltage-dependent gating [ 13 ]. In case of TRPP3 (also named PKD2L1), N533 in the pore loop region is essential for its voltage-dependent inactivation [ 24 ]. Thus, conformational dynamics of the pore region during voltage-dependent inactivation could be conserved among TRP channels.…”
Section: Discussionmentioning
confidence: 99%